And 'all the laws' (Andocides, On the Mysteries 81-2): A Reply to E. Carawan*. (2014) - Joyce, Christopher
Abstract: The normal interpretation of the oath μή μνησικακεĩν in Greek legal terminology is 'to forget past wrongs'. Conventionally, the Athenian amnesty of 403 BC, in which the phrase is best documented, has been understood as an undertaking by both sides to draw a line under the past and prevent revisitation of cases which predated the restoration of democracy in that year. This article defends that view against the revisionist interpretation of E. Carawan in JHS 122 (2002) and CQ 62 (2012), which claims (a) that there was no general amnesty when democracy was restored to Athens, and (b) that the scrutiny of laws which followed was limited to ones affecting the amnesty's beneficiaries. The oath forbade prosecution of all crimes committed in the time of the Thirty or before, and was therefore more than a mere technicality which sealed specific terms of agreement between the warring factions who came to terms. The scrutiny of laws encompassed all the laws of Athens and not a subset pertaining to a limited set of concerns. The revised laws were re-inscribed in the environs of the Stoa Basileios for future consultation.